Strong hydrodynamic processes observed in the Mediterranean Cassidaigne submarine canyon - Brun, Lénaïg; Pairaud, Ivane; Jacinto, Ricardo Silva; Garreau, Pierre; Dennielou, Bernard (Frontiers in Marine Science, 2023)
Introduction Submarine canyons are incisive morphologies that play an important role in the exchange between shallow and deep waters. They interact with the general circulation and induce a specific circulation locally oriented by the morphology. The characteristics of the physical processes at play, the way they interact with each other and the influence of extreme events is still an open question as few observations are available. To answer this question and to improve the representation of submarine canyons in numerical models, it is key to understand the specific circulation patterns and their transitions in these specific environments. Methods This paper presents observations of currents, temperature and turbidity along the Cassidaigne canyon, northwestern Mediterranean Sea. Two oceanographic cruises carried out in 2017 and 2019 gathered data from the outer shelf and canyon head at 100-400 m depth to the base of the continental slope at 1900 m depth. Results and Discussion The circulation in the Cassidaigne area is subject to upwelling and downwelling-favorable winds, to the Northern Current and its associated mesoscale structures and is oriented by the local morphology. Upwellings occur both during stratified and non-stratified conditions. They are triggered by a wind forcing higher than 14 m s–1 and their consecutive relaxations are marked by a counter-current. Near the canyon head and on the shelf, the current orientation depends on the stratification, the wind, the bottom morphology and the general circulation. The mesoscale variability of the Northern Current can lead to its intrusion over the shelf leading to barotropic cross currents over the canyon. At 1700 m depth, a quasi-permanent residual up-canyon flow is observed in a narrow gorge area and can be extrapolated to the canyon body. Finally, turbidity currents were observed for the first time in connection with upwelling events, suggesting the key role of canyons’ internal hydrodynamics on shelf sedimentary processes.